Simultaneous Determination of Essential Oil Components and Fatty Acids in Fennel using Gas Chromatography with a Polar Capillary Column - Najdoska-Bogdanov, Menče; Bogdanov, Jane B.; Stefova, Marina (SAGE Publications, 2015)
Cultivated and wild growing samples of fennel ( Foeniculum vulgare Mill., Apiaceae) from R. Macedonia were studied for their volatiles and fatty acid composition. The main essential oil components isolated via hydrodistillation were: trans-anethole (>80%), estragole (<6%), limonene (<6%), anisaldehyde (<1%) and 0.5 % fenchone. An alternative method for characterization of both the non-polar volatile and non volatile fractions was developed using n-hexane and dichloromethane (3:1, v/v) in a Soxhlet extraction followed by transesterification. The obtained extracts were then characterized and the dominant fatty acid was 18:1 (petroselinic and oleic acid) 75.0–82.8 %, followed by 18:2 (linoleic acid) 10.8–16.2% and other fatty acids: palmitic (4.3–6.9%), stearic (1.2–1.7%) and myristic (0–2.9%). The results for the volatile fraction after Soxhlet extraction and transesterification did not significantly differ from results obtained after hydrodistillation, especially for the main components ( trans-anethole, estragole, fenchone and limonene), implying that the developed method can be used for simultaneous determination of volatiles and fatty acids.